A scalable mechanism for establishing multi-point to multi-point traffic engineering paths in multiprotocol label switching networks. (2016) - Chaitou, Mohamad
Network scalability is a major issue in core networks where multiprotocol label switching (MPLS) is largely deployed. In this paper, we propose a scalable solution for deploying bidirectional multicast trees in MPLS traffic engineering (TE) networks. The deployment of such trees is performed by defining the concept of multi-point to multi-point (MP2MP) TE label switched paths (LSP). Hence, one MP2MP TE LSP can be used instead of a full mesh of point to point (P2P) or point to multi-point (P2MP) TE-LSP in order to support value added applications such as video-conferencing. This leads to reduce the number of TE-LSPs in MPLS-TE networks and hence it improves their scalability. The paper presents the signalling procedures required to incorporate the new proposed MP2MP TE LSP in MPLS networks in addition to a simulation study in order to assess the scalability enhancement introduced by our contribution.